Optimizing resource productivity in soybean-based sequences through long-term crop intensification - Crespo, Cecilia; Novelli, Leonardo Esteban; Wyngaard, Nicolás; Martínez, Roberto Dionisio; Barraco, Miriam Raquel; Gudelj, Vicente Jorge; Barbagelata, Pedro Anibal; Barbieri, Pablo (Elsevier, 2023)
Context: Cropping systems based on a single crop per year, such as soybean monoculture, result in an inefficient use of available resources and low productivity, and are usually related with a negative environmental impact. The intensification of soybean-based cropping sequences can increase resource productivity, enhancing the sustainability of the production systems. Objective: This study aimed to analyse the long-term effect of intensification practices in soybean-based sequences on: i) water and radiation productivity, and ii) soybean yield, in four temperate and fully humid environments with contrasting soil texture. Methods: The study was carried out in four long-term experiments where three cropping sequences were evaluated: soybean monoculture, cover crop (CC) / soybean, and a three-year crop rotation including wheat (Triticum aestivum L.), maize, CC, and soybean. Oat (Avena sativa L.), triticale (x Triticosecale Wittmack), wheat, or rye (Secale cereale L.), were used as CC. Four 3-yr rotation cycles were evaluated between 2007 and 2018. Results: Intensification of cropping sequences increased soybean yield (17%) in one out of four sites, and did not significantly change in the other three sites. Soybean yield varied among cycles at all sites and was positively associated with rainfall during the growing season (r = 0.81). Intensified sequences increased over 40% both water and radiation productivity as compared with soybean monoculture. Despite the different edaphoclimatic characteristics of the evaluated locations, the magnitude of the improvement in the productivity of the resources resulting from the intensification of cropping sequences was similar at all sites. Conclusion: Therefore, in temperate and fully humid environments with contrasting soil texture, the intensification of soybean-based sequences with grasses, CC, and double crops is a feasible alternative to increase the productivity of resources without compromising soybean yield, hence, it should be taken into account by government organizations when developing policies.